THE EFFECT OF AUDIO-VISUAL EDUCATION ON MENOPAUSE SYNDROME IN PREMENOPAUSAL WOMEN - putri, suci zulyani; Kasiati, K; Rijanto, Rijanto; Susilaningrum, Susilaningrum (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
These symptoms can disrupt daily activities and even social life. One approach to preparing women for menopause is by changing their cognitive understanding through education. Audio-visual media is an engaging educational tool because it allows the use of images, graphics, and video animations to visualize the processes and changes occurring in the body during menopause. and attitudes. This study demonstrates that health animated video media. This research design uses a quasi-experiment with a pre-test post-test with control group design. A sample of 37 respondents was selected using Purposive Sampling. The independent variable in the study is Audio Visual, and the dependent variable is knowledge. The instrument used was a pre-post test questionnaire to assess the effect of the media provided, followed by statistical tests using the Wilcoxon Signed Rank Test and Mann Whitney U Test. The results showed that audio-visual media could improve knowledge from poor to good (78.9%). The audio-visual media significantly impacted knowledge, with a p-value of 0.000. The study concluded that education through audio-visual media can enhance premenopausal women’s knowledge. Women with knowledge about menopause syndrome will better understand and feel more confident in managing issues that arise during these changes.